Challenges in overcoming the use of topic fronting among TESL trainees in Malaysia - Megawati Soekarno; Irma Wani Othman; Ameiruel Azwan Ab Aziz; Nik Zaitun Nik Mohamed (Global Academic Excellence, 2021)
Communication strategies include the use of nonverbal or paralinguistic communication strategies such as the use of mime, gestures, facial expressions and eye contact as well as the use of pauses for emphatic expressions could be assimilated. Communication strategies also include the use of verbal communication strategies which need to be learned and developed. One of the verbal communication strategies is a Malaysian classified variety, topic fronting. The issue is that, despite being an achievement communication strategy, topic fronting does not abide by the English language grammatical rule. Thus, a high use of this strategy among ESL learners might affect them adversely especially in academic discourse. This study looked into this strategy among the TESL trainees in two universities from two states in Malaysia. The findings obtained from their focus group discussions (FGD) identified the utilisation of topic fronting in online interactions and methods of overcoming it as well as the inculcation of suitable communication strategies. This study’s findings show a low utilisation of topic fronting (1.142 per thousand words) with the highest theme on the “concession of topic fronting in teaching” at 2.20% average. In the effort to inculcate the TESL trainees’ awareness of their use of topic fronting communication strategy, they need to be involved in active FGDs and be provided with communication strategy trainings on alternative strategies, specifically linguistic strategies like exemplification, circumlocution and paraphrasing.